(untitled) (Acta Scientiarum. Technology, 2023)
Ruthenium complexes have been prepared for several applications, mostly for electrocatalysis, catalytic hydrogenation, energy conversion, photolysis, medicinal chemistry, among other fields. Bipyridine and terpyridine ligands are commonly found in the metal coordination sphere, including ruthenium, largely due to the high stability exhibited by the resulting complex and the possibility of greater stereochemical control during synthesis. The combination of substituted terpyridine ligands with diphosphine ligands to the metal ruthenium occurs to a lesser extent and its catalytic potential has been examined in several studies. This paper describes the synthesis of a new ruthenium (II) aqua complex containing aryl diphosphine and substituted terpyridine ligands: [Ru(L)(totpy)(OH2)](ClO4)2 (L=Ph2PCH2CH2PPh2); (totpy=4´-(4-tolyl)-2,2´:6´,2´´-terpyridine). The synthesis route was conducted in three steps; the final and the intermediate products have shown good reaction yields; the results of the characterization of the aqua complex by cyclic voltammetry, UV-visible spectroscopy and elemental analysis are consistent with the proposed chemical structure.